Plastic pollution within "The Gully" Marine Protected Area of the Scotian Shelf, Northwest Atlantic ... - Kelly, Noreen; Feyrer, Laura; Whitehead, Hal (Zenodo, 2023)
This dataset contains information on plastic particle densities, characteristics (colour, morphology), size, and polymer types collected from seawater in "The Gully" Marine Protected Area between 1990 and 2019. Also included are the characteristics, sizes, and polymer types of ingested debris removed from the stomachs of two Endangered northern bottlenose whales ( Hyperoodon ampullatus ) stranded in Canada in 2019 and 2021. These data appear across 4 tabs in a single .xlsx file, connected by a SampleID column. Please see the following publication for full details: Kelly, N.E., Feyrer, L., Gavel, H., Trela, O., Ledwell, W., Breeze, H., Marotte, E.C., McConney, L. and Whitehead, H., 2023. Long term trends in floating plastic pollution within a marine protected area identifies threats for Endangered northern bottlenose whales . Environmental Research, 227, p.115686. https://doi.org/10.1016/j.envres.2023.115686. ...